Assuring Quality for Non-hospital–based Biologic Infusions in Pediatric Inflammatory Bowel Disease: A Clinical Report From the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition. Issue 4 (April 2018) - Barfield, Elaine; Sockolow, Robbyn; Hoffenberg, Edward; Saeed, Shehzad; Kim, Sandra; Siebold, Leah; Picoraro, Joseph; Moses, Jonathan; Dykes, Dana; Grossman, Andrew; Wahbeh, Ghassan; Park, K.T.
Abstract : ABSTRACT: The primary aim of this Clinical Report by the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition is to provide formal guidance to pediatric gastroenterologists and clinicians, health systems, and insurance payers regarding home- and office-based infusions for biologic therapies in pediatric inflammatory bowel disease. Patients in North America are increasingly denied coverage by payers based on "place of service" codes at hospital-based infusion units where the treating clinicians primarily provide care. A task force with topic expertise generated 8 best practice recommendations to ensure quality of care for pediatric patients with inflammatory bowel disease receiving non-hospital–based biologic infusions. Pragmatic considerations discussed in this report include patient safety, pediatric-trained nurse availability, care coordination, patient-centeredness, shared liability, administrative support, clinical governance, and costs of care.